Reactive Conjugated Polymers: Synthesis, Modification, and Electrochemical Properties of Polypentafluorophenylacetylene (Co)Polymers - Bhebhe, M.; Alvarez de Eulate; Pei, Y.; Arrigan, Damien; Roth, P.; Lowe, Andrew (Wiley - V C H Verlag GmbH & Co. KGaA, 2016)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.(Co)Polymers containing pentafluorophenylacetylene (F5PA) have been prepared for the first time mediated by [Rh(nbd)Cl]2/NEt3 to give materials with properties typical of poly(phenylacetylene)s prepared with this catalyst/co-catalyst combination. It is demonstrated that the F5PA repeat units in these new (co)polymers serve as convenient reactive species for post-polymerization modification with thiols via para-fluoro aromatic nucleophilic substitution reactions to give an entirely new family of novel thioether-functional polyene materials accompanied by absorption maxima shifts of up to 130 nm. Finally, the electrochemical properties of these new fluorinated polyene materials are briefly examined and the distinct difference in behavior of the F5PA homopolymer versus polyphenylacetylene, copolymers, and functional derivatives is highlighted.